Vladimir Korolenko and the Orthodox tradition - V. A. Korshunkov (Шаги, 2023)
In the summer of 1879 Vladimir Korolenko was sent to the east across the Russian North regions to Vyatka province, into exile. He noted in his diary that on the border of the Kostroma and Vyatka provinces (in the village of Dyukovo, present-day Kostroma oblast) people cheerfully and noisily celebrated a certain holiday. According to Korolenko that day was All Saints’ Sunday and the eve of St. Philip’s (Christmas) Fast. However, a calculation of the chronology shows that it was in fact the beginning of St. Peter’s Fast, not St. Philip’s. It turns out that Korolenko made a mistake in counting the weeks after Easter and mixed up two of the four annual Orthodox fasts, calling the summer fast the winter one. Such a strange oversight is a sign of the young writer’s detachment from folk daily life and Orthodox tradition. For this reason, the paper deals with the question of Korolenko’s religiosity, as well as the time and degree of his familiarization with the traditions and everyday life of the Russian people. The evidence of Korolenko’s mindset during some periods of his life, including autobiographical evidence from his book The History of My Contemporary, is considered. We conclude that apparently even Korolenko’s childish religiosity was not overly simple or oriented towards rituals. Subsequently, in his youth, he developed a kind of a non-church religiosity, for which the calendar and other formalities did not matter.